L-Proline Nitrate: An Efficient Amino Acid Ionic Liquid Catalyzed Synthesis of 5-aryl-[1, 2, 4]-triazolidine-3-thiones - Sonawane, Suraj A.; Pore, Dattaprasad M. (Letters in Organic Chemistry, 2022)
An environmentally benign, simple, rapid synthesis of 1,2,4-triazolidine-3-thiones at room temperature is reported using amino acid-derived Brønsted acidic ionic liquid L-proline nitrate [Pro+NO3 -] from aldehyde and thiosemicarbazide in an aqueous medium. A cost-effective and energy-efficient catalyst with the reusability of up to five cycles without significant loss in the catalytic activity makes this protocol superior. A faster reaction and easy work-up with excellent yields are the added advantages of this protocol.
Keywords: Ionic liquid